Enhanced SO2 fluidized adsorption dynamic by hierarchically porous activated coke. Issue 2 (April 2020) - Qie, Zhipeng; Sun, Fei; Gao, Jihui; Pi, Xinxin; Wang, Lijie; Liu, Mingjun; Qu, Zhibin; Zhao, Guangbo
Abstract: Porous materials such as activated cokes have been widely utilized in the adsorption removal of atmospheric SO2 emission. Pore configuration of coke is a key factor affecting its SO2 rapid adsorption dynamics, which is critically important for fluidization adsorption craft. Herein, activated coke adsorbents with typically microporous structure and hierarchically porous structure were prepared by a catalytic physical activation method from Chinese large-reserve Zhundong coal, which were used as model adsorbents to investigate the effect of pore configuration on SO2 fluidized adsorption dynamics. SO2 fluidized-state adsorption experiments indicate that hierarchically porous coke has a more rapid initial adsorption dynamic than microporous type coke, and coke with 44.2% meso-/macropores volume shows the highest initial adsorption rate of 7.37 mg g −1 ·min −1 . Additionally, the fitting of Weber-Morris model provides the dominate factors for SO2 adsorption kinetics in each sub-process: SO2 adsorption capacity of microporous-dominated adsorption stages account for 70%–80% of total, and when it comes close to adsorption saturation, the main dominant factor of kinetic becomes the ratio of meso-/macropores volume. This work is of significance for the application of SO2 adsorption craft in fluidized bed and also provides insight into the role of hierarchically porous configuration in gas molecule rapid adsorption. Graphical abstract: Image 1 Highlights: Model adsorbents for investigating the effect of pore structure on adsorption dynamics are provided. Hierarchically porous coke shows higher initial adsorption rate of SO2 in fluidized bed. Dominate factors of SO2 adsorption dynamics in each sub-process are elucidated.